Faktor-Faktor yang Mempengaruhi Pendapatan Ibu Rumah Tangga yang Bekerja pada Sektor Informal di Kelurahan Dauh Puri Kauh, Denpasar Barat - Wijaya, I Made Adi; Wirathi, I.G.A.P (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 2, No. 5, Mei 2013 (pp. 226-276), 2013)
The purpose of this research was to determine the influence of level of education, hours worked, income and family dependents of housewives who work in the informal sector in Village Dauh Puri Kauh, district West of Denpasar. Sampling is done by proportional sampling techniques. Data collected through observation of non-participation, and structured interview questionnaire. Analytical techniques used was multiple linear regression. From the results of hypothesis testing simultaneously obtained that level of education, hours worked and the amount of income to families dependent housewives who work in the informal sector in village Dauh Puri Kauh. Partially, the third free variable is positive and significant effect on the income of housewives who work in the informal sector in village Dauh Puri Kauh.
Keywords: income of housewives; the informal sector